The effect of repeated freezing and thawing on the suture pull‐out strength in equine arytenoid and cricoid cartilages. Issue 7 (11th July 2022) - Gray, Sarah M.; Gutierrez‐Nibeyro, Santiago D.; Horn, Gavin P.; McCoy, Annette M.; Schaeffer, David J.; Stewart, Matt
Abstract: Objective: To assess the effect of repeated freezing and thawing on the suture pull‐out strength in arytenoid and cricoid cartilages subjected to the laryngoplasty (LP) procedure. Study design: Ex vivo experimental study. Sample population: Ten grossly normal equine cadaveric larynges. Methods: Bilateral LP constructs were created using a standard LP technique. One hemilarynx was randomly allocated to the single freeze and thaw group and the other allocated to the repeated freeze and thaw (3 complete cycles) group. The suture ends of each LP construct were attached to a load frame and subjected to monotonic loading until construct failure. Mean load (N) and displacement (mm) at LP construct failure were compared between groups. Results: All LP constructs failed by suture pull through the arytenoid cartilage. The mean load at failure was similar between groups (118.9 ± 25.5 N in the single freeze and thaw group and 113.4 ± 20.5 N in the repeated freeze and thaw group, P = .62). The mean displacement at failure was similar between groups (54.4 ± 15.1 mm in the single freeze and thaw group and 54.4 ± 15.4 mm in the repeated freeze and thaw group, P = .99). Conclusion: Repeated freezing and thawing did not affect the suture pullout strength of the arytenoid and cricoid cartilages. Clinical significance: Laryngeal specimens that have been subjected to repeated freezing and thawing can be utilized in the experimental evaluation of LP procedures because there is no alteration of the suture pull‐out strength of the relevant cartilages.